PENGARUH KETERLIBATAN EMOSI POSITIF BERUPA AFFECTIVE TRUST DALAM MENGURANGI COMMON MEASURE BIAS PADA EVALUASI KINERJA BALANCED SCORECARDS - , Ai Annisaa Utami, S.Pd.; , Dr. Ertambang Nahatyo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The Effective used of the Balanced Scorecard in the organization will be achieved if the application is a balancing. Lipe and Salterio (2000) proves the existence of cognitive bias as the tendency of the limitations of human cognitive, in form of common measure bias trend of performance evaluation, which is based on common measure, as a result of application of the Balanced Scorecard not to be optimal. This study expands research Salterio Lipe (2000) by adding a variable mitigation involvement top managers with the low managers that begins with the involvement of positive emotions among top managers with the low managers in form of affective trust. About 116 students postgraduated majoring in accounting and management in Islamic University of Indonesia participated in the experiment, with 2x2x2x2 design, split plot of the between 2x2 and 2x2 group within group variable. Hypothesis testing using the Three Way ANOVA with results showing that the common measure and unique measure significantly affects the performance evaluation of the Balanced Scorecard (BSC). In addition, the results do not indicate support for a statistically significant data about the influence of affective reactions in the form of emotional involvement in the form of affective trust in the common measure to mitigate the bias in performance evaluation of the Balanced Scorecard.